Must we defend Nazis? : why the First Amendment should not protect hate speech and white supremacy - Delgado, Richard; Stefancic, Jean (New York University Press, 2018)
"Swirling in the midst of the resurgence of neo-Nazi demonstrations, hate speech, and acts of domestic terrorism are uncomfortable questions about the limits of free speech. The United States stands apart from many other countries in that citizens have the power to say virtually anything without legal repercussions. But, in the case of white supremacy, does the First Amendment demand that we defend Nazis? In Must We Defend Nazis?, legal experts Richard Delgado and Jean Stefancic argue that it should not. Updated to consider the white supremacy demonstrations and counter-protests in Charlottesville and debates about hate speech on campus and on the internet, the book offers a concise argument against total, unchecked freedom of speech. Delgado and Stefancic instead call for a system of free speech that takes into account the harms that hate speech can inflict upon disempowered, marginalized people. They examine the prevailing arguments against regulating speech, and show that they all have answers. They also show how limiting free speech would work in a legal framework and offer suggestions for activist lawyers and judges interested in approaching the hate speech controversy intelligently. As citizens are confronting free speech in contention with equal dignity, access, and respect, Must We Defend Nazis? puts aside clichés that clutter First Amendment thinking, and presents a nuanced position that recognizes the needs of our increasingly diverse society"--Publisher's website.